INFLUENCE OF MARKETING STRATEGY, TRUST, AND PERCEPTION SERVICE QUALITY OF PURCHASING DECISIONS - Yandra Rivaldo; Sabri; Andi Amang; Syarifuddin (Postgraduate Management Journal, 2022)
Consumer purchases in the era of the Covid-19 pandemic as a mode of driving the national economy. This study aims to confirm the theoretical model with empirical data. This study used a survey method with a causal model with multiple linear regression. This study tests the hypothesis used. The population in this study were PT. Buana Cipta Propertindo, amounting to 280 people, sampling using probability sampling method. The results of this study indicate that marketing strategy has a significant effect on purchasing decisions, trust has a significant effect on purchasing decisions, perceptions of service quality have a significant effect on purchasing decisions. Marketing strategy, trust and perceptions of service quality simultaneously influence purchasing decisions.